2002
DOI: 10.1007/s00251-002-0465-5
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of MHC DRB alleles in domestic cats from the United Kingdom

Abstract: The DRB gene of the domestic cat MHC appears to be highly polymorphic, with 71 alleles provisionally reported, based on exon 2 sequence. However, these alleles were reported prior to the adoption of strict criteria for allele identification. In this study, we investigated FLA-DRB exon 2 polymorphisms in a cohort of 33 British domestic cats by polymerase chain reaction (PCR) and clonal sequence analysis. Applying the strict criteria for assigning new alleles as used by the established mammalian MHC nomenclature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 12 publications
0
68
0
Order By: Relevance
“…All these methods have different advantages, but we used the alternative method of reference strand conformation analysis (RSCA). As an automated method, RSCA is suitable for screening large populations reliably, with excellent between-run repeatability even for large fragments (less than 500 bp), and can separate alleles that differ by a single nucleotide (Ramon et al 1998;Kennedy et al 2002).…”
Section: (A) Study Speciesmentioning
confidence: 99%
“…All these methods have different advantages, but we used the alternative method of reference strand conformation analysis (RSCA). As an automated method, RSCA is suitable for screening large populations reliably, with excellent between-run repeatability even for large fragments (less than 500 bp), and can separate alleles that differ by a single nucleotide (Ramon et al 1998;Kennedy et al 2002).…”
Section: (A) Study Speciesmentioning
confidence: 99%
“…Several previous studies reported that relatively high proportions of obtained sequences could be artifacts of PCR amplifications or cloning (Kennedy et al 2002;Longeri et al 2002;Bryja et al 2005). Herein, we used motif-specific PCR, SSCP analysis, and direct sequencing to detect DRB-2 alleles in Ussuri sika deer for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses showed that relatively high proportions of obtained sequences could be artifacts of PCR amplifications (Bryja et al 2005). We considered a new sequence variant as a new allele only when it met the criteria proposed by Kennedy et al (2002): The allele must be identified either in two separate PCRs from the same individual or from PCRs from at least two different individuals. Nomenclature of Ussuri sika deer (Ceni DRB) sequences followed Swarbrick et al (1995).…”
Section: Sequence Characterizations and Phylogenetic Analysismentioning
confidence: 99%
“…The 0.1% threshold was chosen because increasing the threshold resulted in a loss of alleles independently detected in the Ion Torrent and Miseq sequencing experiments, while decreasing the threshold resulted in an increase in erroneous sequences found between replicate samples in this study. We discarded any sequences that were not found in replicate samples unless observed in at least two other individuals after calculating repeatability (Kennedy et al 2002;Galan et al 2010). We calculated repeatability in this study as 1−APD (average percent difference; Yuhki & O'Brien 1990).…”
Section: Mhc Typing Via Next-generation Sequencingmentioning
confidence: 99%